Nanoscale Temperature Sensor with Dual Circular and Square Structures Based on MIM Waveguides - Shubin Yan; Hongfu Chen; Yuanyuan Gao; Weixin Liu; Xiaoran Yan; Aiwei Xu; Taiquan Wu (Photonics)
This paper proposes a refractive index sensor with high sensitivity, which operates based on the Fano resonance phenomenon. The sensor is constructed using a metal–insulator–metal (MIM) waveguide integrated with a double square ring (DSR) configuration, enabling enhanced performance in refractive index detection. The propagation characteristics of the proposed structure are systematically investigated using the finite element method (FEM). Using a control variable method, this study systematically investigates the impact of refractive index changes and specific geometric parameters of the DSR structure on the sensor’s performance. Through the careful optimization of structural parameters, the sensor achieves a peak sensitivity (S) of 2700 nm/RIU along with a figure of merit (FOM) as high as 54. Owing to its simple configuration and high sensitivity, the proposed sensor holds significant potential for applications in temperature sensing and related fields.